(untitled) (Literasi Nusantara, 2025)
Family communication experiences play an important role in shaping how students interpret relationships with parents and express themselves. This study aims to explore the communication experiences of students raised under strict parenting in the context of generational shifts. Using a descriptive qualitative approach with a phenomenological method, data were collected through in-depth interviews with seven students of Universitas Trunojoyo Madura. The findings show that students’ communication experiences are marked by strong parental control, limited dialogue, and predominantly one-way communication. These conditions lead to selective communication, cautious self-expression, conflict avoidance, and adaptive strategies such as withholding information and seeking emotional support outside the family. Generational value differences further intensify communication distance between parents and students.The study concludes that strict parenting shapes students’ communication experiences, self-expression, and social relationships in the university environment.